FINANCIAL STABILITY ANALYSIS OF ERDENET MINING CORPORATION SOE: AN ASSESSMENT OF CAPITAL STRUCTURE AND FINANCIAL RATIOS - Dashzeveg, Bayarjargal (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
This study aims to assess the financial stability of Erdenet Mining Corporation (SOE) and to identify trends in its capital structure and key financial ratios using audited financial statements for the period 2017–2024. Financial stability is evaluated through the equity ratio, coordination coefficient, financial dependence ratio, debt ratio, and current ratio, applying comparative financial analysis. The findings indicate that the company maintains an overall Grade A level of financial stability. However, fluctuations in the current ratio signal certain risks in working capital management and short-term liquidity. The results offer practical implications for optimizing capital structure and strengthening financial policy in state-owned mining enterprises operating in resource-dependent economies.